2018
DOI: 10.1055/s-0038-1673342
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes of Different Subsets in Complexes with Platelets in Patients with Myocardial Infarction

Abstract: Acute myocardial infarction (AMI) is associated with activation of various cells, including platelets that form monocyte–platelet complexes (MPCs). Here, we analysed MPC in vivo and in vitro and investigated the abilities of different monocyte subclasses to form MPC, the characteristics of the cells involved in MPC formation and MPC changes in AMI. We identified MPC by co-staining for platelet antigen CD41a and monocyte antigens CD14 and CD16. Platelet activation was evaluated from expression of phosphatidylse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 51 publications
0
28
0
1
Order By: Relevance
“…Integrins also facilitate platelets to bind to ECM molecules and other cells playing an important role in cell signaling. Since platelet surface markers have, in general, short detectability in human blood, platelet-monocyte aggregates have been detected in several studies as a more sensitive and accurate marker that describes platelet activation and a prothrombotic state in diseases, like advanced atherosclerosis, stable coronary artery disease, acute myocardial infarction, systemic inflammatory and autoimmune disorders, and neoplasms [ 40 , 41 , 42 ]. Similarly, circulating PMPs, that are the most abundant microparticles in the bloodstream (approximately 70–90% of circulating microparticles), are considered as potential biological markers for platelet activation [ 43 ].…”
Section: Platelet Biology and Its Roles In Human Diseasesmentioning
confidence: 99%
“…Integrins also facilitate platelets to bind to ECM molecules and other cells playing an important role in cell signaling. Since platelet surface markers have, in general, short detectability in human blood, platelet-monocyte aggregates have been detected in several studies as a more sensitive and accurate marker that describes platelet activation and a prothrombotic state in diseases, like advanced atherosclerosis, stable coronary artery disease, acute myocardial infarction, systemic inflammatory and autoimmune disorders, and neoplasms [ 40 , 41 , 42 ]. Similarly, circulating PMPs, that are the most abundant microparticles in the bloodstream (approximately 70–90% of circulating microparticles), are considered as potential biological markers for platelet activation [ 43 ].…”
Section: Platelet Biology and Its Roles In Human Diseasesmentioning
confidence: 99%
“…Among all leukocytes, monocytes show the highest affinity for platelet P-selectin, followed by neutrophils; lymphocytes have the lowest affinity [23]. It was shown that among monocytes, different subclasses are involved in PLA, in normal subjects and in patients with myocardial infarction as well [24]. The formation of PLAs involves the release of mediators and mutual activation of both cell types.…”
Section: Inflammation and Platelet-leukocyte Interactionsmentioning
confidence: 99%
“…Upon activation, platelet extracellular vesicles, measuring from 100 to 1000 nm, are released and circulated, and it cannot be ruled out that they form complexes with leukocytes [24]. Since these complexes are CD41-positive, they can hardly be distinguished from PLAs with platelets.…”
Section: General Considerationsmentioning
confidence: 99%
“…22,23 MPA levels were previously found to be higher in ACS patients. 5,24,25 Utilizing this knowledge, coronary-artery aspirates of STEMI patients with a ruptured atheroma were immunostained for platelets and monocytes. The results showed that MPAs remained within the coronary thrombus (►Fig.…”
Section: P-selectin On the Platelet Surface: The Interaction With Rocmentioning
confidence: 99%